MAGNETIC DATA ANALYSIS TO DETERMINE THE SUBSURFACE STRUCTURE OF LESUGOLO GEOTHERMAL POTENTIAL AREA OF ENDE REGENCY - Barry Astro, Richardo
The establishment of Flores as a “Geothermal Island” requires investigation and mapping of geothermal potential. Practically, the presence of geothermal potential in Ende as one of the districts in Flores Island is characterized by many manifestations in form of hot springs, including Lesugolo, Jopu, Detusoko and Kombandaru. In line with the background above, this study was aimed at determining the distribution of local anomalies and subsurface structures from Lesugolo geothermal area in Ende Regency. The initial stage of magnetic data processing was to make several corrections to eliminate the influence of the earth’s main magnetic field and external magnetic fields, as well as the separation of local and regional anomalies. The further stage was to interpret magnetic data both qualitatively and quantitatively. Qualitative interpretation is based on the analysis of local anomaly contour maps supported by geological information in the study area. Quantitative interpretation is done through modeling by using the Mag2DC software. The results of the study have shown that the study area was dominated by medium and low anomaly groups which indicated the demagnetization of rocks due to heat from the geothermal reservoir. There are two fault structures in the study area based on magnetic modeling, namely the normal Lesugolo fault which controls the Lesugolo hot springs and the normal Lise fault. Furthermore, Nida's normal fault was found to control Ae Dhara's hot springs based on qualitative interpretations. Some rock units identified through modeling include tufa rock units, tuffaceous breccia, pyroclastic, and weathered rock units. Majority of the rocks experienced a decrease in the value of magnetic susceptibility.